Tinjauan Hukum Pidana Islam terhadap Sanksi bagi Koruptor di Indonesia dan Jepang - Mahendra, M. Habib; Zulkarnain, Zulkarnain (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2026)
This study examines the effectiveness of corruption sanctions in Indonesia and Japan from the perspective of Islamic criminal law. The research is motivated by the high corruption rate in Indonesia despite severe punishments, while Japan maintains low corruption levels with moderate sanctions. This study fills the gap in comparative research integrating positive law and Islamic criminal law. The objective is to analyze the effectiveness of corruption sanctions and formulate an ideal sanction system based on Islamic criminal law. This research uses a normative legal method with statutory, conceptual, and comparative approaches through library research. The findings reveal that the effectiveness of anti-corruption policies is influenced not only by the severity of punishment but also by legal culture, bureaucratic integrity, law enforcement consistency, and asset recovery mechanisms. The novelty of this study lies in integrating the concept of ta‘zir with modern anti-corruption sanctions. The study implies the importance of reforming Indonesia’s corruption sanction system through stronger asset confiscation and anti-corruption culture.